2014
DOI: 10.15218/zjms.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gonorrhea among adult male with urethritis in Erbil City

Abstract: Introduction disseminated gonococcal infection which presents with arthralgias, tenosynovitis, or arthritis and rush. 1 Gonorrhea control strategies have relied on the use of highly effective and often single dose therapy administered at the time of diagnosis. 2 The appearance and subsequent increased incidence of penicillinase producing Neisseria gonorrhoeae 3 and chromosomally mediated penicillin and tetracycline resistant Neisseria gonorrhoeae 4 in the advanced countries heralded the end of an era in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…According to the ExPASy ProtPram server, the protein's physical properties (Table 4) revealed that it includes 478 amino acids. The most prevalent amino acids in the composition were Ala (37), Arg (30), Asn (23), Asp (26), Cys (3), Gln (47), Glu (55), Gly (20), His (10), Ile (26), Leu (34), Lys (53), Met (7), Phe (17), Pro (11), Ser (28), Thr (15), Tyr (20), Trp (5), Val (11). Its molecular weight is 56206.84 Dalton.…”
Section: Sequence and Similarity Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ExPASy ProtPram server, the protein's physical properties (Table 4) revealed that it includes 478 amino acids. The most prevalent amino acids in the composition were Ala (37), Arg (30), Asn (23), Asp (26), Cys (3), Gln (47), Glu (55), Gly (20), His (10), Ile (26), Leu (34), Lys (53), Met (7), Phe (17), Pro (11), Ser (28), Thr (15), Tyr (20), Trp (5), Val (11). Its molecular weight is 56206.84 Dalton.…”
Section: Sequence and Similarity Informationmentioning
confidence: 99%
“…It is a fastidious [3], non-acid fast [8], oxidasepositive [9] and non-spore-forming bacterium [10]. In addition, it is a non-motile [11] and obligate human pathogen [12] that can thrive aerobically or anaerobically in the presence of nitrite [13]. Gonorrhoea can be asymptotic or develop with symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It is fastidious [ 5 ], non-acid fast [ 6 ], oxidase-positive [ 7 ], and non-spore-forming in nature [ 8 ]. In addition, it is a non-motile [ 9 ] and obligate-human pathogen [ 10 ] that can thrive aerobically or anaerobically in the presence of nitrite [ 11 ]. These diplococci, kidney-shaped bacteria infecting both men and women can cause the sexually transmitted disease (STD) named gonorrhea [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%